Chemistry of Atmospheric Brown Carbon - Laskin, Alexander; Laskin, Julia; Nizkorodov, Sergey A (Chemical reviews, 2015)
The authors examine the chemistry of brown carbon in the atmosphere. Topics discussed include the optical properties of bulk aerosol materials and aerosol extracts and the molecular-level characterization of BrC compounds.